Answer:
a = -1.6b
Step-by-step explanation:
Simplifying
2.3a + -1.8a + 3.5b + -2.7b = 0
Combine like terms: 2.3a + -1.8a = 0.5a
0.5a + 3.5b + -2.7b = 0
Combine like terms: 3.5b + -2.7b = 0.8b
0.5a + 0.8b = 0
Solving
0.5a + 0.8b = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-0.8b' to each side of the equation.
0.5a + 0.8b + -0.8b = 0 + -0.8b
Combine like terms: 0.8b + -0.8b = 0.0
0.5a + 0.0 = 0 + -0.8b
0.5a = 0 + -0.8b
Remove the zero:
0.5a = -0.8b
Divide each side by '0.5'.
a = -1.6b